The Single Column Atmosphere Model Version 6 (SCAM6): Not a Scam but a Tool for Model Evaluation and Development. (16th May 2019) - Gettelman, A.; Truesdale, J. E.; Bacmeister, J. T.; Caldwell, P. M.; Neale, R. B.; Bogenschutz, P. A.; Simpson, I. R.
Abstract: The Single Column Atmosphere Model (SCAM) is a single column model version of the Community Atmosphere Model (CAM). Here we describe the functionality and features of SCAM6, available as part of CAM6 in the Community Earth System Model, version 2 (CESM2). SCAM6 features a wide selection of standard cases, as well as the ability to easily configure a case specified by the user based on a particular point in a CAM 3‐D simulation. This work illustrates how SCAM6 reproduces CAM6 results for physical parameterizations, mostly of moisture and clouds. We demonstrate how SCAM6 can be used for model development through different physics selections, as well as with parameter sweep experiments to highlight the sensitivity of cloud properties to the specification of the vapor deposition process in the cloud microphysics. Furthermore, we use SCAM6 to illustrate the sensitivity of CAM6 cloud radiative properties and precipitation to variable drop number (cloud microphysics properties). Finally, we illustrate how SCAM6 can be used to explore critical emergent processes such as cloud feedbacks and show that CAM6 cloud responses to surface warming in stratus and stratocumulus regimes are similar to those in CAM5. CAM6 has a larger response in the shallow cumulus regime than CAM5. CAM6 cloud feedbacks in the shallow cumulus regime are sensitive to turbulence parameters. SCAM6 is thus a valuable tool for model development, evaluation, and scientific analy sis and an important part of the model hierarchy in Community Earth System Model, version 2. Plain Language Summary: This paper describes and documents a simplified version of a global climate model, which contains only a single column of the atmosphere. This Single Column Atmosphere Model is a very effective tool for developing, evaluating, and understanding the complex interactions and processes that are represented by physical parameterizations in the full model. The paper describes how the single column is constructed and presents detailed comparisons of the single column model to the full three‐dimensional model. Example methods and techniques for using Single Column Atmosphere Model to understand the full 3‐D model are presented, from simple to complex analyses. Key Points: Single Column Models are useful tools for model analysis The SCM in CESM is flexible for development and science analysis Simulated clouds are sensitive to the settings in the turbulence parameterization